1998
DOI: 10.1021/om971119s
|View full text |Cite
|
Sign up to set email alerts
|

A Proton Directly Attacks 1,5-Cyclooctadiene in Bis(1,5-cyclooctadiene)nickel(0) in the Formation of a Keim Type Oligomerization Catalyst

Abstract: Full proton and carbon assignments have been obtained for ((1,4,5-η)-cyclooctenyl)(1,1,1,5,5,5-hexafluoro-2,4-pentadionato)nickel(II) (1), a Keim type ethylene oligomerization catalyst, which is afforded by treatment of bis(1,5-cyclooctadiene)nickel with 1,1,1,5,5,5-hexafluoroacetylacetone. The larger metallacycle formed by nickel and the (1,4,5-η)-cyclooctenyl ligand in 1 is shown to be in a “nickela chair” conformation. The reaction of bis(1,5-cyclooctadiene)nickel with 1,1,1,5,5,5-hexafluoroacetylacetone-d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…This property of nickel is taken advantage of industrially in the Shell higher olefin process, which has a capacity to convert 10 6 tons/year (1990) of ethylene to statistical mixtures of linear medium‐length terminal olefins. Such a polymerization catalyst was prepared by the reaction of (COD) 2 Ni with hexafluoroacetylacetone 41. Recently, Brookhart et al4–8 obtained excellent results by using nickel diimine derivatives activated by MAO.…”
Section: Resultsmentioning
confidence: 99%
“…This property of nickel is taken advantage of industrially in the Shell higher olefin process, which has a capacity to convert 10 6 tons/year (1990) of ethylene to statistical mixtures of linear medium‐length terminal olefins. Such a polymerization catalyst was prepared by the reaction of (COD) 2 Ni with hexafluoroacetylacetone 41. Recently, Brookhart et al4–8 obtained excellent results by using nickel diimine derivatives activated by MAO.…”
Section: Resultsmentioning
confidence: 99%
“…Keim and Peuckert47 showed that Ni(COD) 2 undergoes reaction with Ph 2 PCH 2 CO 2 H, to yield the active ethylene oligomerization catalyst [P,O]Ni(η 3 ‐C 8 H 13 ). Indeed, in the presence of other bidentate ligands with acidic hydrogen atoms, such as hexafluoroacetylacetone, Ni(COD) 2 is also active for ethylene oligomerization 48. Based on deuterium labeling experiments, it was shown that the formation of the active catalyst occurs by direct protonation of an electron‐rich Ni‐coordinated alkene.…”
Section: Discussionmentioning
confidence: 99%
“…They can behave as spectator ligands as in organonickel( II ) complexes which contain three‐electron‐donor anionic P,O chelates such as [Ph 2 PCH 2 C(O)O] − or [Ph 2 PCH−…︁C(−…︁O)Ph] − and which are efficient catalyst precursors for the highly selective oligomerization of ethylene into linear α ‐olefins, a reaction which forms the basis of the industrial Shell Higher Olefin Process (SHOP) 95–102. However, the postulated mechanism of this catalytic reaction does not imply hemilabile behavior of the P,O chelate but instead involves a hydrido nickel species of the type NiH(P,O) which is electronicaly unsaturated and allows the coordination and subsequent insertion of ethylene 96, 97, 103. In palladium( II ) chemistry such anionic P,O chelates may also behave as reactive moieties towards a wide range of electrophilic organic or inorganic reagents.…”
Section: Hemilabile Ligandsmentioning
confidence: 99%